Association of BRCA Mutations and Anti-müllerian Hormone Level in Young Breast Cancer Patients - Son, Kyung-A; Lee, Dong-Yun; Choi, DooSeok (Frontiers in endocrinology (Lausanne), 2019)
Several preclinical and clinical studies have suggested that -mutation carriers may have decreased ovarian reserve. However, data in this area are limited and inconsistent, especially in young breast cancer patients. This study evaluated the association between mutation status and serum anti-Müllerian hormone (AMH) level in young, reproductive-aged patients with breast cancer. Patients ≤ 40 years of age with breast cancer and who had known status and baseline serum AMH level at Samsung Medical Center, Seoul, Korea, were considered for inclusion. A total of 52 mutation carriers (27 and 25 ) and 264 non-carriers were selected for analyses. The serum level of AMH was compared according to presence of a mutation, and linear and logistic regression analyses were performed to evaluate the association between mutation and serum AMH level. No difference was found in clinical characteristics between -mutation carriers and non-carriers. Subjects with any mutation had a significantly lower median AMH than those without a mutation (2.60 vs. 3.85 ng/mL, 32% reduction, = 0.004). Linear regression analysis showed a significant negative association between mutation and AMH level. In addition, logistic regression demonstrated non-significantly increased odds of mutation carriers having AMH < 1.2 ng/mL. However, no difference was found between mutations. Breast cancer patients with mutation have significantly lower serum AMH level. Fertility preservation should be considered more aggressively in young breast cancer patients with mutation.